Exploiting Wireless Links Diversity in Software-Defined IEEE 802.11 Enterprise Wlan - Monir, Md Fahad; Granelli, Fabrizio (IEEE Global Communications Conference (Online), 2020)
Adoption of wireless technologies is rising dramatically. As traffic load is continuously rising with the rapid growth of user scale and mobile services, today's Wireless Local Area Network (WLAN) enterprise is facing a series of crucial challenges such as packet loss, interference, poor bandwidth etc. This is because of the inherent design of the IEEE 802.11 architecture. Enabling Software Defined Networking (SDN) in Wi-Fi enterprise would solve the puzzle of current WLAN technology limitations and ensure high scalability and performance. While standardization is focusing on performance enhancement by evolving the Wi-Fi MAC/PHY protocols, in this work we focus on bandwidth optimization in IEEE 802.11 by using Software Defined Networking (SDN). We analyze various programming abstractions for WLANs and exploit the wireless link diversity in Software Defined Enterprise-WLAN with the support of the 5GEMPOWER-SDN platform. A multiple uplink mechanism between user devices and Access Points (APs) is proposed that allows a remarkable performance improvement in the network in terms of throughput and packet delivery ratio.